Insights into Microbiome and Metabolic Signatures of Children Undergoing Peanut Oral Immunotherapy - Andrea C. Blackman; Santosh Thapa; Alamelu Venkatachalam; Thomas D. Horvath; Jessica K. Runge; Sigmund J. Haidacher; Kathleen M. Hoch; Anthony M. Haag; Ruth Ann Luna; Aikaterini Anagnostou (MDPI AG, 2022)
Background: Peanut oral immunotherapy has emerged as a novel, active management approach for peanut-allergic sufferers, but limited data exist currently on the role of the microbiome in successful desensitization. Objective: We examined the oral and gut microbiome in a cohort of 17 children undergoing peanut oral immunotherapy with the aim to identify the microbiome signatures associated with successful desensitization. We also set out to characterize their fecal metabolic profiles after successful therapy. Methods: Participants gradually built up their daily dose from 2 mg (starting dose) to 300 mg (maintenance dose) within approximately 40 weeks. We collected a buccal and stool specimen from each subject at two different time points: at baseline and post-therapy (1 month after reaching maintenance). The oral (buccal) and gut (fecal) microbiome was characterized based on sequencing of 16S rRNA gene amplicons with Illumina MiSeq. Fecal short chain fatty acid levels were measured using liquid chromatography-tandem mass spectrometry. Results: We report increased alpha diversity of the oral microbiome post-therapy and have also identified a significant increase in the relative abundance of oral Actinobacteria, associated with the desensitized state. However, the baseline gut microbiome did not differ from the post-therapy. Additionally, fecal short chain fatty acids increased after therapy, but not significantly. Conclusion: Our research adds to the limited current knowledge on microbiome and metabolic signatures in pediatric patients completing oral immunotherapy. Post-therapy increased trends of fecal fatty acid levels support a role in modulating the allergic response and potentially exerting protective and anti-inflammatory effects alongside successful desensitization. A better understanding of the microbiome-related mechanisms underlying desensitization may allow development of smarter therapeutic approaches in the near future. Clinical implication: The oral microbiome composition is altered following successful peanut oral immunotherapy, with a significant increase in alpha diversity and the relative abundance of phylum Actinobacteria. Capsule summary: Significant microbiome changes in children completing peanut immunotherapy include increase in alpha-diversity and overrepresentation of Actinobacteria in the oral microbiome, and increased trends for fecal short chain fatty acids, suggesting a protective effect against the allergic response.